Persistence and Residual Toxicity of Some Conventional as Well as Recently Introduced Acaricides against Oligonychus coffeae Nietner (Acari:Tetranychidae) on Tea - Patra, Biswajit (International Journal of Economic Plants, 2024)
An experiment was conducted during March-April, 2018–19 and 2019–20 in the Department of Agricultural Entomology, Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India to evaluate the duration of residual toxicity of five conventional as well as recently introduced acaricides against red spider mite, Oligonychus coffeae on tea. Five acaricides having different mode of actions were selected for the present study. Fenazaquin10 EC, propargite 57 EC, hexythiazox 5.45 EC, spiromesifen 22.9SC and cyflumetofen 20SC were sprayed @ 100, 430, 15,96 and 125 g a.i. ha-1, respectively. Treated leaves were collected from the field and bioassay experiments were conducted in the laboratory. The results revealed that cyflumetofen 20 SC persisted for a longer duration (28 days) with the highest PT value (2347.24) whereas, propargite 57 EC persisted for a relatively short duration (22 days) with lesser PT values (1678.93). Higher LT50 values of 23.83 and 24.26 days were also observed in case of cyflumetofen 20 SC @ 125 g a.i. ha-1 during 1st and 2nd years of study, respectively. The lowest LT50 value was observed in propargite 57 EC @ 430 g a.i. ha-1. Spiromesifen 22.9 SC was found to be the second-best treatment and it showed the LT50 value 22.34 and 22.42 days during 1st and 2nd year of study, respectively.